Democratizing the Middle East? - Fares Center for Eastern Mediterranean Studies (Tufts Archival Research Center, 2005)
Occasional Paper No. 2; A report on the conference Democratizing the Middle East?, January 26-27, 2006, Tufts University, Medford/Somerville, MA.